1999
DOI: 10.1093/pubmed/21.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Management of ischaemic heart disease in primary care: towards better practice

Abstract: Systematic searches of computerized and paper medical records can identify subgroups of patients who will benefit from continuing follow-up in primary care. The results of this study suggest that ischaemic heart disease remains an area where there is scope to improve the management of patients in primary care. Considerable effort will be required from the members of the primary health care team to achieve this objective, particularly in the areas of computerized data collection and in the identification and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Our data suggest that deficiencies in physician knowledge and attitudes regarding atherosclerotic risk factor reduction in patients with PAD contribute to lower rates of risk factor reduction in these patients. Because previous studies demonstrated suboptimal rates of atherosclerotic risk factor reduction for patients with CAD, 24–28 our finding that physicians report even lower rates of risk factor reduction for PAD than for CAD patients is striking.…”
Section: Discussionmentioning
confidence: 71%
“…Our data suggest that deficiencies in physician knowledge and attitudes regarding atherosclerotic risk factor reduction in patients with PAD contribute to lower rates of risk factor reduction in these patients. Because previous studies demonstrated suboptimal rates of atherosclerotic risk factor reduction for patients with CAD, 24–28 our finding that physicians report even lower rates of risk factor reduction for PAD than for CAD patients is striking.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, in the same health setting (UK), we have very diverging reports. A population‐based study reported a CHD incidence of 6.5% (8% of men and 5% of women over 44 years of age) [39], while another reported nearly 3% in subjects over 45 years old and 1.2% in 25–74 years old subjects [40]. In an elderly population in Finland (older than 64 years), the total prevalence of CHD, including angina pectoris, myocardial infarction, post‐coronary artery by‐pass operation or angioplasty or ischaemic ECG findings, was 37.7% in men and 42.0% in women [41].…”
Section: Discussionmentioning
confidence: 99%
“…The national service framework1 requires general practitioners to identify their patients with ischaemic heart disease and to create disease registers by April 2001. These measures are a start towards improving the quality of care for patients with ischaemic heart disease 2–4…”
Section: Introductionmentioning
confidence: 99%